PROMOTIF DAN PREVENTIF PENULARAN COVID 19 PADA MASYARAKAT KELURAHAN BARUGA KOTA KENDARI - Fitri Rachmillah Fadmi; Jumartin Gerung; Sanatang Sanatang (Universitas Mataram, 2023)
The application of health protocols by the community during the Covid-19 pandemic is an effective effort to prevent Covid-19 if discipline is carried out continuously. However, there are still some people who are still indifferent and undisciplined in implementing the covid prevention protocol. The purpose of this community service is to carry out promotive and preventive efforts to increase public knowledge about preventing Covid-19. The target of this community service is the heads of families in three hamlets which are risky areas in Baruga Sub-District as many as 200 heads of families. The method of implementing community service is collaboration with the sub-district government and the community which begins with a survey of the Baruga sub-district regarding risk areas, followed by coordination and communication with RW heads, measuring the knowledge of heads of families, posting posters for preventing Covid-19 in the community and providing Covid prevention tools -19 in the form of masks and hand sanitizers as well as outreach about the importance of taking the Covid-19 vaccine. The evaluation is carried out online via the Google form link which is shared with the target. The results of community service have had a social impact on society in the form of increasing public knowledge about preventing Covid-19.